EXPLORING TEACHERS’ KNOWLEDGE, PRACTICE, AND READINESS FOR A NEW MATHEMATICS CURRICULUM IMPLEMENTATION: Teachers’ knowledge, practice, and readiness - Clement Ayarebilla Ali; Atiah, Desmond Asiniba (Mathematics Research and Education Journal, 2025)
Teachers are generally expected to prepare and implement a new Mathematics curriculum to meet the Millennium Sustainable Development Goal 4 goals. This study assesses teachers’ knowledge, practices, and readiness for the implementation of new Mathematics curricula in Senior High Schools. The researchers adopted the quantitative research approach and a survey research design. The research sample was 76 teachers out of 506 teachers selected through simple random sampling (table of random numbers) from six Senior High Schools. The researchers used Kendall’s tau-b correlation to establish correlations between the components of the mathematics curriculum, means to examine teacher practices, and Chi-square analysis to identify factors. The results showed that many factors hindered the implementation of the new mathematics curriculum. However, teachers were knowledgeable and ready to implement the new standards-based mathematics curriculum. It was therefore recommended that stakeholders consider optimum outcomes within the stipulated period